The implementation of whipping punishment under syariah law in Malaysia: a critical review on the case of Kartika Sari Dewi Shukarno / Mohd Shukri Yaacob…[et al.] - Yaacob, Mohd Shukri; Awang, Musa; Arifin, Afshah; Md. Kassim, Muhamed; Abdul Razak, Abdul Hadi; Adnan, Mohd Faiz (2010)
The word "Syariah" in Arabic word may be defined as 'the road to the watering place, the straight path to be followed. As a technical term, however, the word Syariah was defined by al-Qurtubi as the canon law of Islam, all the different commandment of Allah to mankind. Syariah can be classified into three, namely al-ahkam al- Vtiqadiyyah (sanctions relating to belief), al-ahkam al-akhlaqiyyah (sanctions relating to moral and ethics) and al-ahkam al-lamaliyyah (sanctions relating to the sayings and doings of the individual and his relations with others). Syariah protects and defends life, property, honour, religion and intellect. Therefore, the penal system is essential to guarantee these fundamental human rights as it is the defence system in any society. As whipping is part of methodology to redress moral wrong in society, the aspiration and rules pertaining the exercise of the punishment under the Syariah law are not really understood by laymen. This research attempts to study and answer issues pertaining to Syariah whipping. It attempts to answer the surrounding issues on the subject matter of the studies and suggested several views which may be used as guidance by the administrator of law and other related parties.